Understanding Child Prostitution in Thailand in the 1990s. (24th April 2015) - Montgomery, Heather
Abstract Child prostitution in Thailand became visible in the 1990s. Fueled by accounts by media and nongovernmental organizations, the problem was cast as a straightforward moral issue of coercive parents, helpless child victims, and evil perpetrators. Legal interventions that prosecuted parents and clients were put in place to solve the problem. However, these policies failed to consider ethnographic research on how children and families understood prostitution, and the role it played in their kinship systems and moral economies. In this article, I look at how the problem has been conceptualized. I argue that without a fuller understanding of family relationships and the reciprocal obligations between children and parents, and without listening to children themselves, interventions to protect children were bound to fail.